2020
DOI: 10.1038/s41598-020-58204-2
|View full text |Cite
|
Sign up to set email alerts
|

Causes of fever in Gabonese children: a cross-sectional hospital-based study

Abstract: The causes of infections in pediatric populations differ between age groups and settings, particularly in the tropics. Such differences in epidemiology may lead to misdiagnosis and ineffective empirical treatment. Here, we investigated the current spectrum of pathogens causing febrile diseases leading to pediatric hospitalization in Lambaréné, Gabon. From August 2015 to March 2016, we conducted a prospective, cross-sectional, hospital-based study in a provincial hospital. Patients were children ≤ 15 years with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
3
3
0
Order By: Relevance
“…Indeed, except for HPgV-1, all RNA and DNA viruses reported by our mUNGS analysis represent commonly recognized viral aetiologies of febrile illness in both paediatric and adult populations across all continents. Among viruses known to cause outbreaks in this part of the world, by mUNGS we did not detect any flavivirus or alphavirus sequences, which confirms the PCR results previously reported [5]. Using an unbiased approach such as mUNGS in specific populations, according also to the epidemiological season, will help to characterize viruses causing fever, and provides a surveillance tool for emerging viral diseases.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Indeed, except for HPgV-1, all RNA and DNA viruses reported by our mUNGS analysis represent commonly recognized viral aetiologies of febrile illness in both paediatric and adult populations across all continents. Among viruses known to cause outbreaks in this part of the world, by mUNGS we did not detect any flavivirus or alphavirus sequences, which confirms the PCR results previously reported [5]. Using an unbiased approach such as mUNGS in specific populations, according also to the epidemiological season, will help to characterize viruses causing fever, and provides a surveillance tool for emerging viral diseases.…”
supporting
confidence: 88%
“…In conclusion, our mUNGS investigations support evidence that febrile disease of viral origin among children in Sub-Saharan Africa are frequently associated with "common" viruses. The mUNGS data are concordant with the PCR screening results from a previous study [5] that reported the detection of Human herpesvirus type 6 in the blood of 33% of a subset of 89 patients, Enterovirus and Human rhinovirus in throat swabs of 1.6% of 191 patients each, as well as Rotavirus (11.3% of patients) and Mamastrovirus 1 (4.8% of patients) in stools. Interestingly in the previous study, Human herpesvirus type 6 was detected by PCR in patients without exanthema which suggested past infections or acute infections without apparent skin lesions.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the database has been used in a pilot study to characterize viruses causing fever, and provides a surveillance tool for emerging viral diseases in Gabon [26]. The results are concordant with the PCR screening results from a previous study [27].…”
Section: Validation On Clinical Samplessupporting
confidence: 72%
“…Recent work in LMICs has focused on unravelling the diverse aetiologies of acute febrile illnesses especially in children [7][8][9][10][11][12][13]. Data from outpatient settings are scarce, with a small number of studies describing the relative distribution of bacterial, parasitic and viral agents among acutely febrile patients [7].…”
Section: Introductionmentioning
confidence: 99%